A STUDY ON THE CORRELATION BETWEEN ORGANIZATIONAL ACTIVITY AND ACADEMIC ACHIEVEMENT AMONG STUDENTS - Hasbi Taobah Ramdani; Asep Nizar Faizurahman; Dicky Gunawan (Jurnal Medika Cendikia, 2023)
Student organizations serve as vehicles for the personal growth and development of students, expanding their horizons, augmenting their knowledge, and nurturing their individualities. Academic achievement refers to the degree to which a pupil succeeds in attaining the objectives established for their educational journey. The objective of this research was to ascertain whether or not the achievement of STIKes Karsa Husada Garut students is correlated with their participation in organizations. This research employs quantitative techniques and a cross-sectional design. The research sample for this study comprised 99 individuals, selected using the cluster random sampling method. Methods of data analysis that employ chi-square correlation. The study's findings indicate a significant correlation between organizational activity and student academic achievement, as supported by the odds ratio value of 17.712 and the p value of 0.023, both of which are less than 0.05. These values indicate that there is a noteworthy relationship between organizational activity and student academic achievement